IMPLEMENTASI PROGRAM INDONESIA PINTAR SEKOLAH DASAR DI KECAMATAN TEMBALANG KOTA SEMARANG - Ega Aditya Alfa Riq; Tri Yuniningsih (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2021)
Program Indonesia Pintar, hereinafter referred to as PIP or The Smart Indonesia Program, is government cash assistance provided to students whose parents are not and / or less able to pay for their education. The method used in this research is descriptive qualitative method. The purpose of this research is to see how the implementation of the Smart Indonesia Program (PIP) in Tembalang District Elementary Schools and to analyze the factors that influence its implementation by using the effectiveness of policy implementation through Riant Nugroho's